Legal Analysis of the Implementation of E-Government System in Public Services in Indonesia : (Study in Pasuruan Regency) - Rossa Ilma Silfia (International Publisher, 2025)
This study examines the legal framework and practical implementation of the e-government system in public services within Pasuruan Regency, Indonesia. It aims to analyze the extent to which legal instruments, such as Presidential Regulation No. 95 of 2018 concerning the Electronic-Based Government System (SPBE), have been effectively adopted at the regional level. Utilizing a qualitative research approach, data were collected through interviews, observations, and document analysis. The findings indicate that while Pasuruan Regency has initiated e-government practices, including the use of platforms like SP4N-LAPOR!, challenges persist. These challenges encompass limited human resource competencies, inadequate infrastructure, and insufficient public awareness. Moreover, the study identifies gaps between national regulations and local implementation, highlighting the need for stronger legal mandates and capacity-building initiatives to ensure effective and equitable public service delivery through e-government systems. The research underscores the importance of aligning legal frameworks with practical realities to enhance the efficacy of e-government in regional contexts.